Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

If [tex]$f(x)=\frac{3x}{5}+3$[/tex], which of the following is the inverse of [tex]f(x)[/tex]?

A. [tex]f^{-1}(x)=\frac{5(x-3)}{3}[/tex]

B. [tex]f^{-1}(x)=\frac{3(x-3)}{5}[/tex]

C. [tex]f^{-1}(x)=\frac{5(x+3)}{3}[/tex]

D. [tex]f^{-1}(x)=\frac{3(x+3)}{5}[/tex]


Sagot :

To determine the inverse of the function \( f(x) = \frac{3x}{5} + 3 \), let's go through the process of finding the inverse step-by-step:

1. Start with the given function:
[tex]\[ f(x) = \frac{3x}{5} + 3 \][/tex]

2. Replace \( f(x) \) with \( y \):
[tex]\[ y = \frac{3x}{5} + 3 \][/tex]

3. Swap \( x \) and \( y \):
[tex]\[ x = \frac{3y}{5} + 3 \][/tex]

4. Solve for \( y \):
- Subtract 3 from both sides:
[tex]\[ x - 3 = \frac{3y}{5} \][/tex]

- Multiply both sides by 5 to eliminate the fraction:
[tex]\[ 5(x - 3) = 3y \][/tex]

- Divide both sides by 3 to isolate \( y \):
[tex]\[ y = \frac{5(x - 3)}{3} \][/tex]

Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = \frac{5(x - 3)}{3} \][/tex]

Thus, the correct answer is:
[tex]\[ \boxed{A. \, f^{-1}(x) = \frac{5(x-3)}{3}} \][/tex]